2017
DOI: 10.13045/acupunct.2017085
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and Anti-oxidative Effects of Alpiniae Oxyphyllae Fructus Hot Aqueous Extract in Lipopolysaccharide (LPS)-stimulated Macrophages

Abstract: [Abstract]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Recently, Dantas et al showed that nootkatone inhibited acute and chronic inflammation in mice model (Dantas et al, 2020). Recently, antiinflammatory effect of A. oxyphylla aqueous extract in RAW264.7 cells has been reported (Jo et al, 2017). In our previous study, A. oxyphylla ethanol extract (AOE) showed inhibitory effect on cartilage degradation in a monosodium iodoacetate (MIA)-induced OA animal model and also showed anti-inflammatory and analgesic activities in animal models, and inhibitory effect on proteoglycan degradation from interleukin-1α (IL-1α)-treated rabbit articular cartilage (Lee et al, 2019;Yu et al, 2020).…”
mentioning
confidence: 99%
“…Recently, Dantas et al showed that nootkatone inhibited acute and chronic inflammation in mice model (Dantas et al, 2020). Recently, antiinflammatory effect of A. oxyphylla aqueous extract in RAW264.7 cells has been reported (Jo et al, 2017). In our previous study, A. oxyphylla ethanol extract (AOE) showed inhibitory effect on cartilage degradation in a monosodium iodoacetate (MIA)-induced OA animal model and also showed anti-inflammatory and analgesic activities in animal models, and inhibitory effect on proteoglycan degradation from interleukin-1α (IL-1α)-treated rabbit articular cartilage (Lee et al, 2019;Yu et al, 2020).…”
mentioning
confidence: 99%